Does sharia compliance affect Islamic Banks performance? Evidence from Islamic Banks in Indonesia / Inten Meutiaa, Mohamad Adam and Rulyanti Susi Wardhani - Meutiaa, Inten; Adam, Mohamad; Wardhani, Rulyanti Susi (Universiti Teknologi MARA Selangor, 2019)
Sharia compliance is essential for Islamic financial institutions. This study has two objectives, namely, to determine the level of sharia compliance in Islamic banks in Indonesia, as well as to prove whether sharia compliance affects the performance of Islamic banks in Indonesia. To prove this, the researcher observed the annual report of 11 Islamic banks in Indonesia for the period 2012 to 2016. Sharia compliance is measured through the level of sharia governance in Islamic banks. Sharia governance instruments used to refer to Hasan (2011). While ROA and ROE measure the performance of Islamic banks, content analysis is used to identify sharia governance disclosures in annual reports. The study revealed that on average, the level of sharia compliance of Islamic bank in Indonesia is at the level of best practice while the results of statistical tests prove that there is no significant effect sharia compliance on the performance of Islamic banks both measured by ROA and ROE.